2008
DOI: 10.1016/j.enbuild.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Integration of distributed generation systems into generic types of commercial buildings in California

Abstract: Distributed generation (DG) of combined cooling, heat, and power (CCHP) has been gaining momentum in recent years as an efficient, secure alternative for meeting increasing power demands in the world. One of the most critical and emerging markets for DG-CCHP systems is commercial and institutional buildings. The present study focuses analysis on the main economic, energy-efficiency, and environmental impacts of the integration of three types of advanced DG technologies (high-temperature fuel cells, micro-turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 3 publications
(2 reference statements)
2
32
0
1
Order By: Relevance
“…Researchers have examined the effects of electric load following, thermal load following, baseload operation, and other dispatch strategies [11,25,[32][33][34] as well as dispatch schedules determined through optimization [35,36]. Other efforts have focused on optimization methods that determine the DG installation size as well as the DG operation to minimize total cost [5,24,26,[37][38][39][40][41][42].…”
Section: Economic Dispatch Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have examined the effects of electric load following, thermal load following, baseload operation, and other dispatch strategies [11,25,[32][33][34] as well as dispatch schedules determined through optimization [35,36]. Other efforts have focused on optimization methods that determine the DG installation size as well as the DG operation to minimize total cost [5,24,26,[37][38][39][40][41][42].…”
Section: Economic Dispatch Strategymentioning
confidence: 99%
“…Further studies demonstrate that both FCs and MTGs are best suited for situations with a large and consistent electrical and thermal load as they take full advantage of all the products of the FC or MTG, and that for situations without a consistent thermal load, it is better to employ a generator with higher electrical efficiency [24,25] or to abandon attempts to recover heat in the DG system design [26]. It was also shown that buildings with low electrical load factors and large heating demand were well suited for GT installation [24].…”
mentioning
confidence: 99%
“…Some previous studies have evaluated a variety of building CHP systems (i.e. gas turbines, gas engines, diesel engines and phosphoric acid fuel cells) applied to four generic commercial buildings in Japan [12] or four commercial buildings in California [13].…”
Section: Introductionmentioning
confidence: 99%
“…FC and MTG systems that follow building electrical demand have been studied, showing that both technologies are best suited for situations with large and consistent electrical and thermal demand as they take full advantage of all the FC and MTG products (electricity and heat) and that for situations without a consistent thermal load, it is better to employ a generator with higher electrical efficiency [12,13]. FC systems capable of electric demand tracking were also used to show the need for low DG capital cost and high building thermal demand for economic viability [14].…”
Section: Introductionmentioning
confidence: 99%